2017
DOI: 10.1371/journal.pone.0174578
|View full text |Cite
|
Sign up to set email alerts
|

Independent association between socioeconomic indicators and macro- and micro-nutrient intake in Switzerland

Abstract: BackgroundSocioeconomic differences in diet are rarely assessed with more than one indicator. We aimed to assess differences in macro- and micro-nutrient intake in both sexes according to education, income, and occupation.MethodsWe used data from validated food frequency questionnaire measured dietary intake in 5087 participants (2157 women) from yearly adult population-based cross-sectional surveys conducted from 2005 to 2012 in the canton of Geneva, Switzerland. We used two ANOVA models: age-adjusted and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(83 reference statements)
2
8
0
Order By: Relevance
“…In fact, a high proportion of non-Swiss menuCH participants originates from Italy, France, Portugal, Spain or other southern European countries (37.2%), where the traditional Mediterranean diet is typically consumed. Moreover, in the present study, significantly higher diet quality scores were observed among individuals with a high educational level, a finding in line with previous literature [13,24,25,26,28,42,46]. This could be explained by a high level of food and nutrition literacy in highly educated individuals [13,14,47].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, a high proportion of non-Swiss menuCH participants originates from Italy, France, Portugal, Spain or other southern European countries (37.2%), where the traditional Mediterranean diet is typically consumed. Moreover, in the present study, significantly higher diet quality scores were observed among individuals with a high educational level, a finding in line with previous literature [13,24,25,26,28,42,46]. This could be explained by a high level of food and nutrition literacy in highly educated individuals [13,14,47].…”
Section: Discussionsupporting
confidence: 92%
“…In the elderly, VitD intake was statistically higher among those with a higher education level. Similar observations were reported in two Swiss studies in some population groups [70,71].…”
Section: Discussionsupporting
confidence: 91%
“…Food frequency questionnaire FFQ The FFQ [91] is used during the pre-screening. It consists of a semiquantitative questionnaire existing in French and German, on 80 food items divided in 12 food groups.…”
Section: Additional Questionnairesmentioning
confidence: 99%